Stellar Pulsations. Issue 69 (10th September 2015) - Creevey, O.L.
Abstract : Asteroseismology is a powerful technique that can be employed to determine precise fundamental parameters of stars, such as the radius, mass and age. The data are sensitive to the density structure of the star, so if we combine these with an independently measured radius from interferometry, we can determine the mass with high precision. This is one of the only methods for determining masses of single field stars and with high precision – an otherwise unobservable property. Knowing masses of stars has consequences for exoplanetary characterisation, Galactic population studies and for stars themselves, it allows us to constrain stellar model parameters, yields more precise determinations of ages which thus allows us to calibrate age-rotation relations as well as setting stellar constraints on the age of our own Galaxy.